2021
DOI: 10.2147/ndt.s306585
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders of Neurocysticercosis: Narrative Review

Abstract: Neurocysticercosis, the most common type of neuroparasitosis, is a condition in which the central nervous system (CNS) is infested with the pork tapeworm Taenia solium cysticercosis' larvae. Neurocysticercosis is the most widespread parasitic CNS disease worldwide, affecting more than 50 million individuals. As neurocysticercosis is prevalent in developing countries, the growing number of migrants and travelers increases prevalence in developed countries. Possible neuropsychiatric manifestations are depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 92 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…Second, A comprehensive survey of patients and pigs is to be conducted, in order to understand the distribution of the disease, screen carriers of cysticercosis, and finding out the incidence of disease, so as to prevent the spread of infection in the population and the development of cysticercosis. The specific measures of this method are to carry out publicity, popularize the knowledge of prevention and control, so that people can grasp the clinical manifestations and main examination methods of tapeworm disease and cysticercosis, and at the same time, doctors should find cysticercosis pigs according to the patient's place of residence and whether the root of the tongue of nearby live pigs has cysts as the basis for the disease [5]. Third, When people find that they have excreted nodal tablets in their stools, pimples on the body, epilepsy, Figure 2.…”
Section: Prevention Of Taeniasis and Cysticercosismentioning
confidence: 99%
“…Second, A comprehensive survey of patients and pigs is to be conducted, in order to understand the distribution of the disease, screen carriers of cysticercosis, and finding out the incidence of disease, so as to prevent the spread of infection in the population and the development of cysticercosis. The specific measures of this method are to carry out publicity, popularize the knowledge of prevention and control, so that people can grasp the clinical manifestations and main examination methods of tapeworm disease and cysticercosis, and at the same time, doctors should find cysticercosis pigs according to the patient's place of residence and whether the root of the tongue of nearby live pigs has cysts as the basis for the disease [5]. Third, When people find that they have excreted nodal tablets in their stools, pimples on the body, epilepsy, Figure 2.…”
Section: Prevention Of Taeniasis and Cysticercosismentioning
confidence: 99%
“…The symptoms of NCC mimic psychiatric and neurological disorders in up to 15% of infected patients, including affective disorder, schizophrenia, depression, headaches, seizures, and epilepsy [ 4 ]. Annually, there are more than 2,300 admissions due to NCC in the United States, and only 2% of seizure cases admitted are discovered to be attributed to NCC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Annually, there are more than 2,300 admissions due to NCC in the United States, and only 2% of seizure cases admitted are discovered to be attributed to NCC [ 5 ]. We found very few publications that consider NCC's psychiatric symptoms; however, studies have shown that patients with NCC show a decline in the quality of life, depression, and moderate cognitive impairment [ 4 ]. It has been suggested, by a prior study on the quality of life in patients with NCC, that the seizures and epilepsy caused by NCC affect the psychosocial aspects of life, leading to depression and anxiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human cysticercosis is endemic in most developing countries and frequently attacks the human central nervous system (CNS), causing a variety of neurological symptoms called neurocysticercosis (NCC) (13). It is reported that more than 50 million people worldwide infected with larva of T. solium and developed into NCC, with 0.1 percent of mortality (14).…”
Section: Introductionmentioning
confidence: 99%